Validasi Metode Penetapan Kadar Kurkumin pada Tablet Ekstrak Rimpang Temulawak (Curcuma xanthorrhiza Roxb.) dengan KCKT - Choliq, Ramadhan Idam; Hardani , Prisma Trida; Sinulingga, Amanda Safithri (Journal of Pharmaceutical and Sciences, 2024)
Curcuma rhizome contains antioxidants, where the compound that acts as an antioxidant is curcumin. Temulawak rhizome extract tablets as a supporting supplement for the treatment process of diseases such as liver function disorders, ulcers, coughs, diarrhea, and constipation. This study was conducted to obtain a valid method in determining curcumin levels in temulawak rhizome extract tablet preparations by HPLC. The stages carried out in this study were the preparation of the mobile phase, standard preparation, HPLC optimization, sample preparation, and method validation. Validation consists of several parameters, namely linearity, LOD and LOQ, selectivity, precision, and accuracy. In the curcumin standard all parameters have met the requirements, linearity (r = 0.9975), LOD (6.5420 mg/L) and LOQ (21.8067 mg/L), selectivity (Rs = 1.7139). In brand A curcumin tablets, precision (RSD < 5.7%), while for accuracy (recovery 90-107%). The selected method can be used for the determination of curcumin content in temulawak rhizome extract tablet preparations.